2020
DOI: 10.1136/bmjopen-2019-034699
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a hospital-based integrated model of eye care for diabetic retinopathy assessment: a multimethod study

Abstract: ObjectivesDiabetic eye disease is a leading cause of blindness but can be mitigated by regular eye assessment. A framework of issues, developed from the literature of barriers to eye assessment, was used to structure an examination of perceptions of a new model of care for diabetic retinopathy from the perspective of staff using the model, and health professionals referring patients to the new service.DesignMultimethod: interviews and focus groups, and a separate survey.SettingA new clinic based on an integrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Similar core components exist in shared care initiatives used in eye care and other health disciplines. This includes supervision, training or upskilling workforce [ 20 , 22 ]; well-defined scope of practice [ 20 , 23 ]; protocols [ 20 , 22 , 23 ]; and service integration [ 21 , 22 , 24 ]. Information technology is recognized as an essential component for team communication [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar core components exist in shared care initiatives used in eye care and other health disciplines. This includes supervision, training or upskilling workforce [ 20 , 22 ]; well-defined scope of practice [ 20 , 23 ]; protocols [ 20 , 22 , 23 ]; and service integration [ 21 , 22 , 24 ]. Information technology is recognized as an essential component for team communication [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such schemes might also offer a better patient experience by delivering care in more acceptable locations, with greater access to transport or reduced travel times (27). Another benefit of these schemes is that they offer enhanced communication between referring providers, which is often a shortcoming in hospital care (8,31). In the current study, patients held a firm expectation that this was already happening, which might be attributed to their passive trust that the healthcare providers act in their best interest to guide them to appropriate care.…”
Section: Discussionmentioning
confidence: 99%
“…Readers are used for analyzing the pictures of the fundus and identifying structural features of DR and also seek predictions about the risk of loss of sight based on its severity [ 23 ]. It has been observed that there is a reduction in the number of patients with vision loss pertaining to DR due to improved and timely examination of people with diabetes along with an improvement in glycemic control [ 24 ].…”
Section: Reviewmentioning
confidence: 99%